2008
DOI: 10.1002/j.2050-0416.2008.tb00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Procedures for Resveratrol Analysis in Beer: Assessment of Stilbenoids Stability through Wort Fermentation and Beer Aging

Abstract: Three resveratrol extraction procedures were compared in beer. Two-step pre-cleaning with toluene and cyclohexane allows 76% trans-resveratrol recovery by solid-phase extraction (SPE) before RP-HPLC-MS/MS analysis. This procedure proved much more efficient than liquid/liquid extraction, which requires solvents that are too hydrophobic for stilbenoids. SPME-GC-MS, where the main limiting factor is non-reproducibility from fibre to fibre, is an interesting alternative for resveratrol quantification in complex mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…It has also been employed for the analysis of volatiles and aroma compounds in soy sauce 1,16,34 . However, the main limiting factor of SPME is non-reproducibility from fibre to fibre 13 . Thus if possible, the same fibre should be employed during an experiment in order to ensure the accuracy of results.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been employed for the analysis of volatiles and aroma compounds in soy sauce 1,16,34 . However, the main limiting factor of SPME is non-reproducibility from fibre to fibre 13 . Thus if possible, the same fibre should be employed during an experiment in order to ensure the accuracy of results.…”
Section: Resultsmentioning
confidence: 99%
“…Later, trans-resveratrol and trans-piceid were identified in red sorghum grains, which are used in African countries for local production (Bröhan et al, 2011). Stilbenoids, specifically trans-resveratrol, cis-resveratrol, trans-piceid, and cis-piceid, have also been found in beer (Jerkovic et al, 2008;Chiva-Blanch et al, 2011).…”
Section: Stilbenoidsmentioning
confidence: 98%
“…Two procedures based on solid-phase microextraction (SPME) combined with GC-MS and HPLC-MS/MS, with atmospheric pressure chemical ionization (APCI), were compared for analysis of both stilbenoids (Jerkovic et al, 2008). The results showed that SPME-GC-MS allows the direct determination of transresveratrol (detection limit (LOD): 5 μg/l), without previous pre-cleaning and long extraction steps, although a derivatization by silylation has to be performed due to the low volatility of this stilbenoid.…”
Section: Stilbenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Muñoz-González et al (2012) carried out a liquid-liquid extraction of phenolic acids using ethylacetate in acidic condition prior to their analysis by gas chromatography coupled to mass spectrometry (GC-MS). A similar approach was conducted for the extraction of resveratrol and other stilbenoids from beer (Jerkovic et al 2008) before their analysis by liquid chromatography coupled to mass spectrometry (LC-MS)…”
Section: Liquid-liquid Extractionmentioning
confidence: 99%